RANCANG BANGUN SISTEM MONITORING SUHU, INTENSITAS CAHAYA, SISA PAKAN DAN MINUM KANDANG ANAK AYAM PETELUR BERBASIS INTERNET OF THINGS (IOT) - Labib Ammar Fadhali; n/a Nurussa’adah; Ali Mustofa (Jurnal Mahasiswa TEUB, 2023)
Poultry farming, especially laying hens, is a promising subsector of agribusiness that plays a vital role in improving the welfare of farmers and national development. The development of this poultry farming aims to increase livestock production to meet the needs of food, nutrition, and farmer income. In Indonesia, East Java is the largest producer of chicken eggs due to high consumption demand and the high nutritional content of eggs from laying hens. However, poultry productivity is influenced by various factors, such as breed, feed, nutrition, health, and cage conditions. Manual monitoring of the conditions of broiler chicken cages is considered inefficient, leading to the need for research to create an efficient and flexible broiler chicken cage monitoring system. The monitoring system employs sensors for temperature, light intensity, water level, and weight, capable of monitoring cage conditions in real-time through an Android smartphone using the Blynk platform. The test results show that each sensor exhibits high accuracy: temperature sensor 99.46%, light intensity sensor 99.37%, weight sensor 99.07%, and water level sensor 99.79%. Additionally, data transmission and notifications on Blynk were successful without any discrepancies, allowing data sent by the ESP32 to be accurately and promptly displayed on the LCD and Blynk when connected to the internet. Keywords: Temperature, Light Intensity, Food Weight, Water Level, Blynk